Research on the Value of Listed Companies in the Global Automotive Industry - Lei Caihao; She Feng (SHS Web of Conferences)
The valuation of the current automotive industry has been undergoing some significant changes due to the rapid shift of market trends. The rise of electric vehicles (EVs) through government policies and its technological enhancements on batteries has much to offer on the table to be a substantial opponent of the traditional automobile companies. This research focuses on analyzing the market value of the leading automakers such as Tesla, BYD, and Toyota by examining the financial metrics, which include Profitability, Liquidity, Efficiency, and Growth ratios. While also evaluating the strengths and weaknesses of these industry leaders. The finding suggests that cost efficiency and supply chain control play an important role in one’s valuation. Though Tesla is in the lead in the technological invitations, meanwhile, BYD benefits from its well-integrated production chain, which drastically cuts the cost down. Toyota, on the other hand, maintains its stability through hybrid technology. These findings provide insights to investors, policymakers, and industry leaders in better understanding how the shift to electric vehicles impacts the financial landscape of the automotive industry.